Development and Psychometric Evaluation of A Physics Creative Thinking Assessment Instrument Based on Classical Test Theory for Senior High School Students - Baiq Nabila Saufika Zainuri; Syahrial Ayub; Aris Doyan; Gunawan Gunawan (Indonesian Journal of Teacher Education, 2022)
Creative thinking is an essential competency in physics education; however, assessment instruments with adequate psychometric quality remain limited. This study aimed to develop and evaluate a physics creative thinking assessment instrument for senior high school students based on the Classical Test Theory (CTT) framework. A research and development approach was employed involving 40 eleventh-grade science students at SMAN 1 Kediri. The instrument consisted of eight essay items representing four dimensions of creative thinking: fluency, flexibility, originality, and elaboration. Psychometric evaluation included empirical validity using the Pearson Product Moment correlation, reliability using Cronbach's Alpha, and item analysis through difficulty and discrimination indices. The results indicated that seven of the eight items met the empirical validity criteria, while one item required revision. The instrument demonstrated high internal consistency with a Cronbach's Alpha coefficient of 0.823. Overall, the item difficulty and discrimination indices showed that the instrument possessed satisfactory item characteristics. These findings indicate that the developed instrument has good psychometric quality based on the Classical Test Theory framework and is suitable for assessing senior high school students' creative thinking skills in physics learning.